Articular Cartilage Endurance and Resistance to Osteoarthritic Changes Require Transcription Factor Erg. Issue 10 (23rd September 2015) - Ohta, Yoichi; Okabe, Takahiro; Larmour, Colleen; Di Rocco, Agnese; Maijenburg, Marijke W.; Phillips, Amanda; Speck, Nancy A.; Wakitani, Shigeyuki; Nakamura, Takashi; Yamada, Yoshihiko; Enomoto‐Iwamoto, Motomi; Pacifici, Maurizio; et al.
Abstract : Objective: To determine whether and how the transcription factor Erg participates in the genesis, establishment, and maintenance of articular cartilage. Methods: Floxed Erg mice were mated with Gdf5‐Cre mice to generate conditional mutants lacking Erg in their joints. Joints of mutant and control mice were subjected to morphologic and molecular characterization and also to experimental surgically induced osteoarthritis (OA). Gene expression, promoter reporter assays, and gain‐ and loss‐of‐function in vitro tests were used to characterize molecular mechanisms of Erg action. Results: Conditional Erg ablation did not elicit obvious changes in limb joint development and overall phenotype in juvenile mice. However, as mice aged, joints of mutant mice degenerated spontaneously and exhibited clear OA‐like phenotypic defects. Joints in juvenile mutant mice were more sensitive to surgically induced OA and became defective sooner than operated joints in control mice. Global gene expression data and other studies identified parathyroid hormone–related protein (PTHrP) and lubricin as possible downstream effectors and mediators of Erg action in articular chondrocytes. Reporter assays using control and mutated promoter‐enhancer constructs indicated that Erg acted on Ets DNA binding sites to stimulate PTHrP expression. Erg was up‐regulated in severely affected areas in human OA articular cartilage but remained barely appreciable in areas of less affected cartilage. Conclusion: The study shows for the first time that Erg is a critical molecular regulator of the endurance of articular cartilage during postnatal life and that Erg can mitigate spontaneous and experimental OA. Erg appears to do this through regulating expression of PTHrP and lubricin, factors known for their protective roles in joints.